A polygenic risk score predicts atrial fibrillation in cardiovascular disease. (18th August 2022) - Marston, Nicholas A; Garfinkel, Amanda C; Kamanu, Frederick K; Melloni, Giorgio M; Roselli, Carolina; Jarolim, Petr; Berg, David D; Bhatt, Deepak L; Bonaca, Marc P; Cannon, Christopher P; Giugliano, Robert P; O'Donoghue, Michelle L; et al.
Abstract: Aims: Interest in targeted screening programmes for atrial fibrillation (AF) has increased, yet the role of genetics in identifying patients at highest risk of developing AF is unclear. Methods and results: A total of 36, 662 subjects without prior AF were analyzed from four TIMI trials. Subjects were divided into quintiles using a validated polygenic risk score (PRS) for AF. Clinical risk for AF was calculated using the CHARGE-AF model. Kaplan–Meier event rates, adjusted hazard ratios (HRs), C -indices, and net reclassification improvement were used to determine if the addition of the PRS improved prediction compared with clinical risk and N-terminal pro-B-type natriuretic peptide (NT-proBNP). Over 2.3 years, 1018 new AF cases developed. AF PRS predicted a significant risk gradient for AF with a 40% increased risk per 1-SD increase in PRS [HR: 1.40 (1.32–1.49); P < 0.001]. Those with high AF PRS (top 20%) were more than two-fold more likely to develop AF [HR 2.45 (1.99–3.03), P < 0.001] compared with low PRS (bottom 20%). Furthermore, PRS provided an additional gradient of risk stratification on top of the CHARGE-AF clinical risk score, ranging from a 3-year incidence of 1.3% in patients with low clinical and genetic risk to 8.7% in patients with high clinical and genetic risk. The subgroup of patients with high clinical risk, high PRS, and elevated NT-proBNP had an AF risk of 16.7% over 3 years. The C -index with the CHARGE-AF clinical risk score alone was 0.65, which improved to 0.67 ( P < 0.001) with the addition of NT-proBNP, and increased further to 0.70 ( P < 0.001) with the addition of the PRS. Conclusion: In patients with cardiovascular conditions, AF PRS is a strong independent predictor of incident AF that provides complementary predictive value when added to a validated clinical risk score and NT-proBNP. Structured Graphical Abstract: Structured Graphical Abstract Classification of study population by genetic, clinical, and biomarker risk for atrial fibrillation (AF). PRS, polygenic risk score; CHARGE-AF, Cohorts for Heart and Aging Research in Genomic Epidemiology for Atrial Fibrillation (risk score including age, height, weight, systolic blood pressure, diastolic blood pressure, current tobacco use, antihypertensive medication use, diabetes, heart failure, and prior myocardial infarction). Rates of incident AF by genetic, clinical, and biomarker risk categories are shown.